Numerical study of hybrid through plate connections to CFST columns - Twizere, Moussa; Taşkin, Kıvanc (Penerbit Universiti Kebangsaan Malaysia, 2022)
The use of concrete-filled steel tube (CFST) columns is highly encouraged nowadays in modern multistory structures. The major reason is the extensive resistance offered by the hollow steel column to high compression. Nevertheless, further studies and data are desirable to exhaustively characterize these members and their connections to other members, such as beams. This paper investigated the behavior of concrete-filled columns connected to I-beams by through plates. Three simple types of plate connections (easy to assemble and construct) were proposed and evaluated. The behavior of these connections was examined under static loading by using advanced finite element based software (ABAQUS). The modeling techniques used in this study were validated by comparing the numerical results of a through plate connection model with the results of two relevant experimental studies. The proposed connections were classified as semi-rigid connections according to Eurocode-3. These connections were able to move the plastic hinge away from the column panel zone. The maximum plastic rotations of all connection types were greater than 40 mrad. The failure mode, and moment-rotation curves of the concrete-filled column to steel beam connections were discussed based on numerical results. The influence of through plate material and through plate thickness were evaluated via a parametrical study.